'Stuffd up with books': the bookshops and business of Thomas Payne and Son, 1740–1831. Issue 3 (2nd September 2019) - Fallon, David
ABSTRACT: This article reconstructs the London bookshops run by Thomas Payne and his son, Thomas Payne Junior, first at the Mews Gate and then at Schomberg House, Pall Mall. As well as retailing and publishing, the shops became venues for sociable gatherings and served a public function akin to the coffee house in Jürgen Habermas's influential account of the public sphere. Indeed, Payne's shop at the Mews Gate gained a reputation as the first 'literary coffee-house'. The article recovers important connections between the print production, retail, and sociability in the Paynes' shops, exemplifying changes in the market for rare books and the bookseller's rising respectability from the mid-eighteenth century to the early decades of the nineteenth century.